Determinan Turnover Intention Karyawan Pada UD. Cipta Angso Duo di Kota Jambi - Niken, Niken Meisa Putri (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to reveal the influence of job satisfaction, workload, job stress, and work environment on employees' turnover intention at UD. Cipta Angso Dua in Jambi City. This research uses a quantitative approach with primary data collected through a survey method using a questionnaire. The population in this study is all employees of UD. Cipta Angso Dua in Jambi City, totaling 35 people, with a saturated sampling technique. The data analysis method used is multiple linear regression with SPSS 25 software. The results show that job satisfaction and job stress have a significant negative effect on turnover intention, while workload and work environment have a significant positive effect on employees' turnover intention at UD. Cipta Angso Dua in Jambi City. These findings indicate that the company needs to increase job satisfaction and reduce workload and job stress to decrease employees' turnover intention. A more conducive work environment is also needed to create a comfortable and supportive work atmosphere. Theoretically, this study supports expectancy theory.